Videopedia management and business series [kasetvideo] (Dubai : Al Kabas Video Services)
Vol. 1. Managing stress -- v.2. The heart: attack/counter attack v.3. Speaking effectively: to one or one thousand -- v.4. Verbal communication: the power of words -- v.5. Perception -- v.6. The power of positive reinforcement -- v.7. A new look at motivation -- v.8. Performance appraisal: the human dynamics -- v.9. Decisions -- v.10. Group dynamics: groupthink -- v.11. Career development: a plan for all seasons -- v.13. The effective use of power and authority -- v.14. Business, behaviourism and the bottom line -- v.15. /Creative problem solving: how to get better ideas -- v.16. Problem solving strategies: synectivs approach -- v.17. Why people buy -- v.18. Selling to tough customers -- v.19. A case of working smarter, not harder -- v.20. What is MBO.